2020
DOI: 10.1523/eneuro.0035-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Biophysical Signatures across Molecularly Defined Medial Amygdala Neuronal Subpopulations

Abstract: The medial amygdala (MeA) is essential for processing innate social and non-social behaviors, such as territorial aggression and mating, which display in a sex-specific manner. While sex differences in cell numbers and neuronal morphology in the MeA are well established, if and how these differences extend to the biophysical level remain unknown. Our previous studies revealed that expression of the transcription factors, Dbx1 and Foxp2, during embryogenesis defines separate progenitor pools destined to generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 82 publications
(117 reference statements)
3
28
0
Order By: Relevance
“…In agreement with our results, extensive previous work has implicated Foxp2 gene function in the multi-fold processes of chromatin regulation, activity-dependent plasticity, and dendritic morphology (French and Fisher, 2014 ; Co et al, 2020 ). As the MeA is a highly sexually dimorphic brain region (Gegenhuber and Tollkuhn, 2020 ; Matos et al, 2020 ), it is possible that Foxp2 may be required to regulate these processes differently in males and females. Unraveling the underlying neuronal and circuit mechanisms of the Foxp2 -dependent control of innate behaviors as well as the sex differences in the function of Foxp2 will likely be an exciting area of future investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with our results, extensive previous work has implicated Foxp2 gene function in the multi-fold processes of chromatin regulation, activity-dependent plasticity, and dendritic morphology (French and Fisher, 2014 ; Co et al, 2020 ). As the MeA is a highly sexually dimorphic brain region (Gegenhuber and Tollkuhn, 2020 ; Matos et al, 2020 ), it is possible that Foxp2 may be required to regulate these processes differently in males and females. Unraveling the underlying neuronal and circuit mechanisms of the Foxp2 -dependent control of innate behaviors as well as the sex differences in the function of Foxp2 will likely be an exciting area of future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In the amygdala, Foxp2 is highly expressed in both the intercalated neurons (ITCs), which are associated with fear conditioning, and the medial subnucleus (MeA), which is essential for processing olfactory cues that trigger innate (unlearned) behaviors such as mating, aggression, parenting, and predator avoidance (Lischinsky et al, 2017 ; Kuerbitz et al, 2018 ; Lischinsky and Lin, 2020 ). Our previous studies using either immunohistochemistry to label Foxp2+ cells or Cre-based fate mapping to tag Foxp2+ cells and their descendants revealed that Foxp2+ and Foxp2 -lineage neurons in the MeA are a molecular and electrophysiologically distinct subpopulation of inhibitory output neurons (Carney et al, 2010 ; Lischinsky et al, 2017 ; Matos et al, 2020 ). Our work further revealed that Foxp2+ and Foxp2 -lineage neurons are activated by innate reproductive and aggressive behaviors in a sex-specific manner and display molecular and intrinsic electrophysiological differences between males and females (Lischinsky et al, 2017 ; Matos et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together these data show that sex-specific differences in intrinsic properties emerge at adulthood in BLA pyramidal neurons and that male BLA neurons display a higher excitability than female neurons at the same age. Action potentials in BLA principal neurons diverge at pubescence Changes in spike trains and excitability could partly be explained by changes in ion channel conductance which generate the different phases of action potentials (Hunsberger & Mynlieff, 2020;Matos et al, 2020;Y. Zhang et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…We found two types of MeApd GABA neurons with remarkably low rates of AP-firing even with high current injections (Suppl. Figure 5, AP-firing types 1 and 2; see also Lischinsky et al, 2017;Matos et al, 2020). In these neurons, optogenetic stimulation under ChR2 was often not able to trigger APs during the second half of trains (Suppl.…”
Section: Chr2 Causes Large Plateau Depolarizations Ap Amplitude Decrements and Increased Local Inhibitionmentioning
confidence: 96%